WORDWALL AS AN ONLINE ASSESSMENT PLATFORM IN TEACHING ENGLISH - Naufal Ilyas Saputra; Haris Dibdyaningsih; Rizki Ramadhan (STKIP AL HIKMAH SURABAYA, 2023)
There needs to be an adjustment in choosing learning media. If it is still implemented in schools with face-to-face learning, teachers can easily display their teaching media to support the teaching and learning processes. One program, branded Wordwall, is said to be capable of helping students acquire and expand their reading. The Wordwall application is a website-based online program that can use as both a teaching tool and an assessment. In this 21 st century world, English will still play vital roles and gained more prestige in education Students will feel more motivated to learn English, especially in reading, and will have an outstanding learning experience with an intriguing page display with a variety of colors. Additionally, by creating questions with presumed, the Wordwall application makes it incredibly simple for teachers to acquire and customize English reading content.